The perception of tourist information sources in domestic tourism: Serra da Estrela Destination - Dias Oliveira, Nelson (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Communication and the tourism industry have walked together since the advent of tourism, converged together on the web, and have been reinventing themselves in social media and recent platforms and apps. Tourist destinations have always needed some kind of communication to make them known. There are several sources of tourism information that oscillate between formal and informal, institutional and commercial… conveyed in various media. In this paper we intended to reflect on the importance of information sources in domestic tourism, taking as an example the destination Serra da Estrela, Portugal.